FLUKTUASI HARGA MINYAK DUNIA DAN PENCAPAIAN SUSTAINABILITAS FISKAL INDONESIA - Suharsih, Sri (Kinerja: Jurnal Bisnis dan Ekonomi, 2013)
This research aims to measure the fi scal risks and contingent liabilities caused by increasing world oilprices in terms of fi scal sustainability. Analysis was performed by using the Balance Sheet Approach (BSA)and the mean variance analysis to calculate the fi scal risk. Furthermore, in relation to fi scal sustainability itwas examined whether the fi scal risks that occur was through structural changes or not during the years 1977-2008 with the fl uctuating oil price conditions. It was analyzed by using stationary test application by inserting astructural break elements, developed by Zivot Andrews (ZA test).The results show that increases in oil prices caused the fi scal risk in Indonesia, this can be seen from thecalculation of networth with BSA and the mean variance analysis showed negative results, especially whenIndonesia became a net oil importing country and increase oil price was very high approaching U.S. $ 100 /barrel. ZA test results showed that there had been structural changes in risk variables, such conditions occurwhen the world oil price has increased to nearly 100 U.S. dollars / barrel. This shows that the increase in oilprices could disrupt the achievement of fi scal sustainability.Keywords: Fiscal Risk, Zivot Andrews (ZA) test, Balance Sheet Approach (BSA)